LOSS OF DIRECTORS' RESPONSIBILITY FOR TERMINATION OF EMPLOYMENT RELATIONS WITH EMPLOYEES DUE TO THE COMPANY'S BANKRUPTCY - Syahputra, Dzikrul Hadi (Inspiring Law Journal, 2025)
Limited Liability Company (PT) as an independent legal entity operates through its organs, with the board of directors having a central role in managing the company. In business practices that are full of dynamics and uncertainty, directors often face the risk of lawsuits for decisions that result in losses for the company. To protect directors who act in good faith, the business judgment rule doctrine is present as a principle that provides legal protection for directors from liability for company losses, including in the context of bankruptcy that results in termination of employment with employees. This study aims to analyze the application of the business judgment rule doctrine in Law Number 40 of 2007 concerning Limited Liability Companies, examine the differences between ultra vires actions that are beneficial and the application of the business judgment rule, and analyze the accountability of directors for termination of employee employment due to company bankruptcy. The application of the business judgment rule doctrine in Indonesia is reflected in Article 97 paragraph (5) of the Limited Liability Company Law, which provides protection for directors who have carried out their duties in good faith, with caution, without conflict of interest, and in accordance with the authority granted. This study found that ultra vires actions that benefit the company cannot be equated with the business judgment rule, because these actions still violate the limits of authority in the articles of association.